PENGARUH PERENCANAAN ANGGARAN, PELAKSANAAN ANGGARAN, DAN KUALITAS KINERJA SDM TERHADAP TINGKAT PENYERAPAN ANGGARAN DI DIREKTORAT JENDERAL X TAHUN ANGGARAN 2024 - Verdina Wardhiningtyas; Eneng Sugihyanty; Yohannes Ferry Cahaya (UNIVERSITAS DHARMAWANGSA, 2026)
Budget absorption is a crucial performance indicator for government agencies. However, the phenomenon of year-end budget accumulation (fiscal dumping) and inconsistent realization between the first and second semesters still persists within the Directorate General X. Although the 2024 budget realization reached 89.08%, there remains a significant remaining budget, indicating a need to evaluate the influencing factors. This study aims to analyze the influence of budget planning, budget execution, and human resources (HR) performance quality on budget absorption at the Directorate General X for Fiscal Year 2024. Using a quantitative approach with multiple linear regression analysis through the use of SPSS version 26 software, the study involved 70 financial management respondents comprising Commitment Making Officials (PPK), Treasurers, and other financial management staff selected through purposive sampling. The results show that simultaneously, budget planning, budget execution, and HR performance quality have a significant positive effect on budget absorption, contributing 81.8%. Partially, all three variables significantly influence budget absorption, with budget execution being the most dominant factor. The study concludes that budget absorption optimization is highly dependent on the synergy between planning, execution discipline, and HR competence. To obtain more comprehensive results, further research should explore other determinant variables and extend the study's scope to more than one Directorate General. Keyword: Budget Absorption, Budget Planning, Budget Execution, Human Resource Performance Quality